2007
DOI: 10.1073/pnas.0709650104
|View full text |Cite
|
Sign up to set email alerts
|

Runx2 deficiency and defective subnuclear targeting bypass senescence to promote immortalization and tumorigenic potential

Abstract: The osteogenic Runt-related (Runx2) transcription factor negatively regulates proliferation and ribosomal gene expression in normal diploid osteoblasts, but is up-regulated in metastatic breast and prostate cancer cells. Thus, Runx2 may function as a tumor suppressor or an oncogene depending on the cellular context. Here we show that Runx2-deficient primary osteoblasts fail to undergo senescence as indicated by the absence of ␤-gal activity and p16 INK4a tumor suppressor expression. Primary Runx2-null osteobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 42 publications
6
70
1
Order By: Relevance
“…Work by Zaidi and colleagues (12) has demonstrated that RUNX2 is important for the expression of p21, p16, and p19, which mediated the antiproliferative mechanisms in osteoblasts by the blockade of cyclin action. (16,17) It was clearly noticeable that at 0.5% FCS, the rise in RUNX2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Work by Zaidi and colleagues (12) has demonstrated that RUNX2 is important for the expression of p21, p16, and p19, which mediated the antiproliferative mechanisms in osteoblasts by the blockade of cyclin action. (16,17) It was clearly noticeable that at 0.5% FCS, the rise in RUNX2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since cyclin D1 is involved in the G 0 /G 1 transition, our results suggest that inhibition of RUNX2 activity accelerates exit from G 1 and entry into S phase but does not change cell exit from G 0 . Moreover, Zaidi and colleagues (12) have shown that primary RUNX2 À/À osteoblasts exhibited loss of p21, p19, and p16, which all regulate the activity of the cyclin/cyclin-dependent kinase complex. (12) In fact, p16 and p19 reportedly inhibit cyclin D (19,20) and p21 inhibits cyclins D, E, and A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HDACs), co-regulators (e.g. TLE-1, a homolog of groucho), YAP and SMADs (Zaidi et al, 2002;Zaidi et al, 2004) Disruption of RUNX protein subnuclear targeting alters transcriptional programs and compromises cell growth and differentiation (Zaidi et al, 2006), reflecting its pathological linkage to acute myelogenous leukemia and breast and prostate cancers (Zaidi et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%